Kinetics of depolymerization of paraformaldehyde obtained by thermogravimetric analysis (2015)
ABSTRACT: Solid paraformaldehyde is a source of formaldehyde that is preferred when anhydrous conditions in chemical processes are required. In this contribution, several depolymerization models were proposed for paraformaldehyde in powder (PFP) and prills (PFS), and they were validated with experimental thermogravimetric analysis (TGA). For description of PFP depolymerization, a model of a single step was adequate, and for PFS the best model included two simultaneous mechanisms. Kinetic models were determined using Master Plot method; for PFS, small intervals of conversion were used in order to obtain the best model at each finite point of the progress of reaction. Apparent activation energies (Ea) were obtained by isoconversional methods. For PFP, Ea was 31.7 kJ mol-1 and the model corresponded to Avrami-Erofeyev 2 (A2). For PFS decomposition, the activation energy of the two mechanisms was Ea = 105.4 kJ mol-1 for a contracting volume (R3) model and Ea = 48.4 kJ mol-1 for the Avrami-Erofeyev model.